Consumer purchase intention towards environmentally friendly vehicles: an empirical investigation in Kuala Lumpur, Malaysia - Rafia, Afroz; Masud, Muhammad Mehdi; Akhtar, Rulia; Islam, Md. Ashraful; Duasa, Jarita (Springer, 2015)
This paper examines whether attitudes towards electric vehicles (ATEVs), subjective norms (SNs) and perceived behavioural control (PBC) have significant associations with consumer purchase intention (PI) and the purchase behaviour of environmentally friendly vehicles (EFVs). The resultsfromthesurveyquestionnairesareanalysedusingconfirmatory factor analysis (CFA) and structural equation modelling (SEM). The findings of this paper indicate that ATEV, SN and PBC significantly influence PI. This finding also indicates that environmental consequence and individual preferences do not influence the PI of the respondents. We found that Malaysian car owners are largely unaware of the greenhouse effects on the environment or attach to it little importance, which is reflected in their PI towards EFVs. The outcomes of this study could help policymakers design programmes to influence attitudes, subjective norms, perceived behavioural control and purchase behaviour to prevent furtherairpollutionandreduceCO2 emissionsfromthetransportation sector.